A Revisit to the Hydrogen Desorption/Absorption Behaviors of LiAlH4/LiBH4: Effects of Catalysts - Pattaraporn Sridechprasat (Energies, 2012)
The hydrogen desorption/absorption behaviors of LiAlH4/LiBH4 with a focus on the effects of catalysts, namely TiCl3, TiO2, VCl3, and ZrCl4, were investigated using a thermal-volumetric apparatus. The hydrogen desorption was performed from room temperature to 300 °C with a heating rate of 2 °C min−1. The LiAlH4–LiBH4 mixture with a molar ratio of 2:1 decomposed between 100 and 220 °C, and the hydrogen desorption capacity reached up to 6.6 wt %. Doping 1 mol % of a catalyst to the mixture resulted in the two-step decomposition and a decrease in the hydrogen desorption temperature. All the doped samples provided lower amountz of desorbed hydrogen than that obtained from the undoped one. No hydrogen absorption was observed under 8.5 MPa of hydrogen pressure and 300 °C for 6 h. Despite the fact each of the catalysts may affect the hydrogen storage behaviors of the mixture differently, none resulted in a change in the sample reversibility.